(I)moralidade e censura: prazeres desviantes e sexualidade na obra de Cassandra Rios (1968-1977) - Nóbrega, Isabela Silva (2015)
This dissertation discusses the treatment given to the works of writer Cassandra Rios who with the production of an erotic literature intensified the fight against immorality in social behavior and the defense of the good morals between the years 1968 and 1977. Supported by conservative groups of Brazilian society, the professionals involved to the repression mechanism of public entertainment (DCDP) worked more rigorously on cultural manifestations of the country. The analysis prioritized the comprehensiveness of speeches that built a Cassandra Rios profile connected to transgression practices and degeneration of moral standards. From reading of veto opinions and some books of the author I identified the elements that justified the charge of breaking of the codes required by the prior censorship law. Such historical and fictional representations provide the opportunity to rethink the combinations of control of the literary production and the institutional repression through tactics resistance of Cassandra Rios front the prohibitions. Thus, I highlight the existence of a kind of "tradition of censorship" to the behaviors treated as immoral represented in literary works as motivation of the "censorial outbreak" which tried to contain the spread of pornography in the 70's. This study was developed in the Postgraduate Program in History at the Universidade Federal da Paraíba in accordance with the analysis of the research line called "Teaching of History and Historical Knowledge".